THE IMPACT OF LOCAL ECONOMIC DEVELOPMENT THROUGH COMMUNITY-BASED TOURISM ON ECONOMIC WELFARE OF THE COMMUNITY IN TAMANSARI VILLAGE, BANYUWANGI, EAST JAVA, INDONESIA - Harod Rahmad Novandi; Isbandi Rukminto Adi (Indonesian Journal of Social Work, 2021)
According to the data of the Central Bureau of Statistics (BPS) East Java (2017), the percentage of poor people in East Java was 11.20 percent or 4.41 million people. This figure was still high compared to the national average poverty rate which was 10.12 percent of the total population. Poverty in the East Java region is dominated by rural poverty as many as 2.95 Million People and the other was due to urban poverty as much as 1.46 million people. In Tamansari Village, a rural settlement area at the foot of Mount Ijen makes the village the spearhead of public services, cultural centers, and local economic drivers. This research discusses the impact of local economic development (LED) through community-based tourism (CBT) in Tamansari village, Banyuwangi Regency, Indonesia. The research area and using qualitative approach with descriptive research. While collecting data using in-depth interviews with 30 informants consisting of local government, local economic organizations, and local communities. The results of this research show a positive impact, the first impact of LED on work behaviour , in the second impact of LED on Family Financial Management the conditions, The third impact of LED on the Improvement of the Family Economy, The fourth impact of led on changes in mindset and behavior of stakeholders in the community. Based on the results of this research note that local economic development through community-based tourism in Tamansari Village prioritizes the interests of local communities. This condition should be carried out sustainably and be connected with human, social and cultural, and physical resources.